Odinofagia diduga disebabkan oleh penyempitan esofagus akibat konsumsi glifosat-surfaktan dalam jumlah kecil: Laporan Kasus - Simanjuntak, Arya Marganda; -, Harianto; Nasution, Ibrahim Irsan (Cermin Dunia Kedokteran, 2026)
Introduction: Glyphosate-surfactant is a non-selective, broad-spectrum systemic herbicide widely used in agriculture, forestry, and industry. It is frequently ingested in suicide attempt and depending on the ingested dose, may cause local caustic injury, systemic toxicity, or even death. Case: A 32-year-old man presented to the emergency department (ED) with throat pain and difficulty swallowing food for 2 days after ingesting approximately 5 mL of glyphosate-surfactant. Examination found hyperemic pharyngeal arch and oropharynx edema (Mallampati III). Laboratory results revealed leukocytosis, renal function, and electrolyte abnormalities. After gastric lavage, antibiotics, NSAIDs, and a liquid diet, the patient improved and was able to eat independently. Discussion: Even in small volumes (5 mL), glyphosate-surfactant, a caustic substance, can cause irritation and inflammation of the esophageal tract and progress to esophageal stricture. Conclusion: Small amounts of glyphosate-surfactant compound ingestion caused esophageal strictures, affecting the patient's ability to eat and causing discomfort, despite no kidney or respiratory damage.